Preaching Through Islamic Education: The Challenge of Education of Millennial Muslim Character - Noviansah, Ahmad (Journal of Indonesian Islamic Studies, 2025)
This study aims to find out the challenges in preaching through Islamic education for the millennial generation. In Muslim society, the word preaching, both as a concept and an activity, is often identified as education (tarbiyah) on the grounds that in preaching there is an element of education and in education there is an element of preaching, especially since both activities do not recognize age. This millennial era is interpreted by some experts as the back to spiritual and moral or back to religion . Namely the period of returning to spiritual, moral and religious teachings. The challenge of the current millennial generation is how to change the information obtained by someone into meaningful knowledge. The main assets of the millennial generation in this era are ideas and creativity, research and findings supported by science. The Millennial Generation is a generation terminology that is currently widely discussed by many circles in the world in various fields. Millennials or also known as the Millennial Generation or Generation Y are demographic groups ( cohorts ) after Generation X. Social researchers often group the generation born between the 1980s and 2000s as the millennial generation. It can be said that the millennial generation is the current young generation who are currently in the age range of 21 to 41 years.